Factors influencing sustainable practices adoption among food and beverage SMEs in Peninsular Malaysia - Mat Yusuf, Umi Nadirah (2019)
SMEs in manufacturing sector has a crucial role in contributing to Malaysian economy specifically, the food and beverages sector in fulfilling the increasing demand for food in Malaysia. However, there is a rising concern regarding issues on the environmental degradation caused by the aforementioned sector. Sustainable manufacturing practices have been identified as an approach to minimize the effect of manufacturing activities towards environmental degradation. Thus, the specific objectives of this study were to examine the sustainable manufacturing practices undertaken by the SMEs manufacturers; to identify the association between business profile of SMEs manufacturers and the adoption of sustainable manufacturing practices; to determine the factors that motivate SMEs manufacturers to adopt sustainable manufacturing practices and to predict the most influential factors influencing the SMEs manufacturers towards the adoption of sustainable manufacturing practices. A total of 378 food and beverages SMEs were selected as respondents and the questionnaires were distributed. Only 375 of the questionnaires were used for analysis, while three questionnaires were discarded due to the incomplete information. The data was analysed using several statistical analyses, namely descriptive analysis, mean ranking analysis, Chi-Square analysis, factor analysis, and logistic regression analysis. Based on the descriptive analysis, majority of the food and beverages SMEs participated in this research have annual sales turnover between RM300000 to RM15 Millions, which are categorized as small SMEs. Mean ranking analysis showed that most of the SMEs reasoned they have never received summons on environmental problems as the basis to not adopt sustainable practices. Chi-square analysis was conducted to investigate the association between business profile of food and beverages SME‟s and the adoption of sustainable practices. The result showed that adoption of sustainable practices has positive significant association with region of SMEs. The factor analysis revealed four main factors that influenced the adoption of sustainable practices, namely knowledge, economic benefit, stakeholder demand, and financial incentives. Finally, the logistic regression analysis indicated that knowledge, annual sales turnover, and region were the most influential factors that influenced the adoption of sustainable practices among food and beverages SMEs. Based on the findings from the present study, it is highly recommended to involve related agencies to improve the adoption of sustainable practices by providing training programmes to extend the knowledge on sustainable practices among food and beverages SMEs.